Seeker / 10 - Tiernan, Cate (Tiernan, Cate. Sweep, 2002)
Hunter reluctantly leaves Morgan behind when he receives news about the location of his parents who disappeared years earlier, but he arrives to find his mother has died and his father unwilling to allow her spirit its freedom.